Madagascar's extraordinary biodiversity: Threats and opportunities - Ralimanana, Hélène; Perrigo, Allison L; Smith, Rhian J; Borrell, James S; Faurby, Søren; Rajaonah, Mamy Tiana; Randriamboavonjy, Tianjanahary; Vorontsova, Maria S; Cooke, Robert S C; Phelps, Leanne N; Sayol, Ferran; Andela, Niels; et al. (Science (New York, N.Y.), 2022)
Madagascar's unique biota is heavily affected by human activity and is under intense threat. Here, we review the current state of knowledge on the conservation status of Madagascar's terrestrial and freshwater biodiversity by presenting data and analyses on documented and predicted species-level conservation statuses, the most prevalent and relevant threats, ex situ collections and programs, and the coverage and comprehensiveness of protected areas. The existing terrestrial protected area network in Madagascar covers 10.4% of its land area and includes at least part of the range of the majority of described native species of vertebrates with known distributions (97.1% of freshwater fishes, amphibians, reptiles, birds, and mammals combined) and plants (67.7%). The overall figures are higher for threatened species (97.7% of threatened vertebrates and 79.6% of threatened plants occurring within at least one protected area). International Union for Conservation of Nature (IUCN) Red List assessments and Bayesian neural network analyses for plants identify overexploitation of biological resources and unsustainable agriculture as the most prominent threats to biodiversity. We highlight five opportunities for action at multiple levels to ensure that conservation and ecological restoration objectives, programs, and activities take account of complex underlying and interacting factors and produce tangible benefits for the biodiversity and people of Madagascar.
Keywords: rostliny; ohrožené druhy; Humans; Plants; biodiverzita; Madagascar; zvířata; Bayesova věta; Madagaskar; Biota; Bayes Theorem; společenstvo; savci; Endangered Species; Animals; Biodiversity; Mammals; lidé